ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø© Ø¬Ø§Ù…Ø¹Ø© Ù…Ø§ØªØ§Ø±Ø§Ù… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ù„Ù„Ø¹Ø§Ù… Ø§Ù„Ù…Ø¹Ù‡Ø¯ÙŠ 2021/2022 â€œLa Taskutâ€Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙƒØªØ§Ø¨ - Fatia Rahmanita; Wirawan Jamhuri (Lughatu Ad-dhat, 2023)
In ma'had al-Jami'ah there are many alumni of public schools who have never studied Arabic before, therefore ma'had al Jami'ah held a language program called "Lailatul Lughah" with the aim of providing Arabic language learning (Vocabulary and Daily Conversation). This research focuses on how the process of using the book " La Taskut " and its application in learning Arabic to students of Ma'had al - Jami'ah Mataram State Islamic University. The method used in this research is descriptive method.Â  The results of the research that can be concluded by researchers through the process of interviews, documentation and direct observation are student learning at Ma'had al-Jami'ah Mataram State Islamic University using the book "La Taskut" In learning Arabic at Ma'had al Jami'ah the students faced and the solutions were: a) students who did not like Arabic because they had not studied Arabic before.Â  And the solution is that the teacher gives them practice and teaches them at the basic stage, b) Students have not applied the learning in their daily life and the solution is that the teacher continues to provide examples and motivate students to apply it in their daily life.